VEGETABLE GARDENS IN THE GAMBIA - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Horticultural crop production has long been recognised as a means of diversifying the production base of the Gambian economy, for increasing the self-reliance of the country's producers and, very importantly, for improving the food security...